Peri Partum Cardiomyopathy: A Case Report - Aloysius Suryawan; Theresia Monica Rahardjo; Fabianus Ferdian Damario; Alicka Octorevia Witjaksono; Angela Mulyana Sugiaman; Kellen Clementine; Nafisya Dhira Bella; Winda Permata Sari; Yoshua Adhi Nicholaus; Yovita Hamdani; I Made Putra Rena (Medical Clinical Update, 2023)
Cardiomyopathy that appears around the end of pregnancy or in the first few weeks after delivery is known as peripartum cardiomyopathy (PPCM). The pathogenesis of PPCM is unknown, however a number of factors, including viral myocarditis, an atypical resistance to pregnancy, an odd reaction to the increased hemodynamic weight of pregnancy, hormone interactions, ill health, aggravation, and apoptosis, are thought to contribute to this illness.